DMF Activates NRF2 to Inhibit the Pro-Invasion Ability of TAMs in Breast Cancer - Li, Ying; Jia, Yaxu; Xu, Yurong; Li, Kan (Frontiers in Oncology, 2021)
Tumor -associated macrophages (TAMs) in breast cancer tissues can account for more than 50% of the cells in the tumor immune microenvironment. High TAM density is associated with poorer clinical prognosis due to the ability of TAMs to promote tumor growth, progression, and metastasis. Therefore, targeting TAMs is a promising therapeutic strategy. In the present study, we found that the pro-tumor invasive ability of TAMs in the co-culture system was significantly inhibited under DMF treatment, and further in vitro results confirmed that DMF acts by reducing reactive oxygen species (ROS) production in TAMs. We examined the anti-tumor effects of DMF in vivo by using an in situ 4T1 cell inoculation model and a spontaneous MMTV-PyMT tumor model. The results showed that DMF remained able to significantly inhibit tumor metastasis and increase T cell infiltration into the tumor microenvironment in vivo. Mechanistically, the activation of Nrf2 is essential for DMF to perform its function. In conclusion, DMF can function as an anti-cancer agent targeting TAMs in breast cancer.